The Influence of Entrepreneurship Knowledge, Soft Skills and Internshipon Working Readiness(A Case Study at SMK Karya Bhakti Brebes) - Astuti, Iryana Dewi; Murwatiningsih, Murwatiningsih; Yanto, Heri (Universitas Negeri Semarang, 2017)
The educated unemployment in Indonesia caused by some factors such as the lack of knowledge and skill or soft skill as well as lack of job training so that the graduates become unemployment who do not have readiness to work. The purpose of the study is to know and analyze the influence of enterpreneurship knowledge, soft skill and job training to job readiness. The method used the survey, description, and correlation. Students of SMK Karya Bhakti grade eleventh. The sample of the research is 80 respondents by using proportional random sampling. The method of data collecting is by using quesionnaires. The data are analyzed by using linier regression. The result of the research shows that there is an influence of enterpreneurship knowledge to job readiness, partially obtained value of 6.484, the effect of soft skill on the job readiness is 1.498, and the influence of job training to job readiness partially obtained value of 2.205. simultaneously the influence of enterpreneurship knowledge, soft skill, job training on job readiness based on F test obtained value 17.330